Edukasi dan Demo Masak Pada Ibu Hamil dan Menyusui Tentang ASI Eksklusif dan Stunting di Kelurahan Rungkut Tengah Kota Surabaya - Diah Riski Hedianti; Yolanda Eggy Varera; Qonita Rachmah (Universitas Airlangga, 2023)
Background: Breast milk contains various nutrients needed for infants. The coverage of babies receiving exclusive breastfeeding in 2021 in Surabaya City is 72.91%. A high level of knowledge determines whether or not it is easy for mothers to understand and absorb information about exclusive breastfeeding. The higher the mother's level of knowledge, the higher the mother's ability to absorb information about exclusive breastfeeding. Objectives: Provide support and build confidence to pregnant and breastfeeding women, and increase knowledge regarding the benefits of exclusive breastfeeding for children up to 2 years of age. Methods: The implementation of this community service includes education with lecture methods using power point and leaflets media, followed by sharing/discussion, and cooking demonstrations with the menu Mustard Greens Rolls with Tofu Carrot Chicken. The success of the activity is marked by indicators of increased knowledge as measured by the results of pre and post tests. Result: Data analysis showed that the average value of knowledge before (pre test) and after (post test) was given education increased, and the p-value result was 0.000 <0.05, meaning that there was a significant difference in the level of knowledge of pregnant and breastfeeding women before and after education. Conclusions: Providing education using the lecture method using power point media about exclusive breastfeeding and stunting leaflets can effectively increase the knowledge of pregnant and breastfeeding women, so that educational activities and cooking demonstrations can be carried out continuously and routinely. It is expected that pregnant and breastfeeding women can exclusively breastfeed their children until the age of 2 years as an effort to reduce the prevalence of stunting and prevent stunting in the future.